2015
DOI: 10.1111/pedi.12314
|View full text |Cite
|
Sign up to set email alerts
|

Clinical presentation and memory function in youth with type 1 diabetes

Abstract: Objective While cerebral edema and diabetic ketoacidosis (DKA) in type 1 diabetes (T1DM) have well-described acute effects on cognition, little is known about the impact of clinical presentation on longer-term cognitive outcomes. We hypothesized that clinical factors (degree of hyperglycemia exposure and DKA) at the time of diagnosis would relate to cognition within 3.5 months later in children with T1DM. Methods Cognitive testing was performed on children 7–17 years old with T1DM (n=66) within 3.5 months of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
43
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 33 publications
6
43
0
3
Order By: Relevance
“…Despite the high prevalence of these complications at diagnosis in childhood, few studies have investigated their longer-lasting impact on the brain. In a previous paper, we found an association between DKA and hyperglycemia at diagnosis and memory performance approximately 3 months post-diagnosis in children with type 1 diabetes (21). Moreover, a recent study found that DKA at diagnosis was associated with differences in white matter diffusivity and volume days afterwards, most of which resolved by 6 months.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…Despite the high prevalence of these complications at diagnosis in childhood, few studies have investigated their longer-lasting impact on the brain. In a previous paper, we found an association between DKA and hyperglycemia at diagnosis and memory performance approximately 3 months post-diagnosis in children with type 1 diabetes (21). Moreover, a recent study found that DKA at diagnosis was associated with differences in white matter diffusivity and volume days afterwards, most of which resolved by 6 months.…”
Section: Introductionmentioning
confidence: 82%
“…Animal studies have shown that hyperglycemia and DKA can lead to varying degrees of dysfunction in the hippocampus (4446) and human studies have linked severity of clinical presentation in youth with type 1 diabetes to decreased delayed memory performance, a critical function of the hippocampus (5, 21, 22). Unfortunately, in our dataset, we had few subjects with both valid imaging and cognitive data to perform correlations between these two outcomes with adequate power.…”
Section: Discussionmentioning
confidence: 99%
“…These differences in memory function were present even when there was no clinically apparent cerebral edema. We previously found that, after adjusting for age, sex, and socioeconomic status, youth with type 1 diabetes and a DKA event at diagnosis performed worse on a long-delay memory task 4 months after diagnosis compared to sibling control subjects (42). Another study found that youth presenting with DKA at diagnosis had poorer performance on a verbal delayed memory task and a mental state task within 48 hours of diagnosis compared to those presenting without such an event at diagnosis (43).…”
Section: Cognitive Function and Risk Factorsmentioning
confidence: 98%
“…13 Among patients without obvious neurologic decline during treatment for diabetic ketoacidosis, subtle neurologic alterations are often present after recovery, including deficits in memory, attention, and IQ 47 and changes in cerebral microstructure. 4,8,9 …”
mentioning
confidence: 99%